#### Answer

x=-1

#### Work Step by Step

Simplifying
13x + 6 = 6x + -1
Reorder the terms:
6 + 13x = 6x + -1
Reorder the terms:
6 + 13x = -1 + 6x
Solving
6 + 13x = -1 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
6 + 13x + -6x = -1 + 6x + -6x
Combine like terms: 13x + -6x = 7x
6 + 7x = -1 + 6x + -6x
Combine like terms: 6x + -6x = 0
6 + 7x = -1 + 0
6 + 7x = -1
Add '-6' to each side of the equation.
6 + -6 + 7x = -1 + -6
Combine like terms: 6 + -6 = 0
0 + 7x = -1 + -6
7x = -1 + -6
Combine like terms: -1 + -6 = -7
7x = -7
Divide each side by '7'.
x = -1
Simplifying
x = -1